2019
DOI: 10.1519/ssc.0000000000000481
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Current Literature on the Utility of the Functional Movement Screen as a Screening Tool to Identify Athletes' Risk for Injury

Abstract: THE FUNCTIONAL MOVEMENT SCREEN (FMS) IS A POPULAR MOVEMENT SCREENING TOOL USED BY REHABILITATION PROFESSIONALS AND STRENGTH AND CONDITIONING SPECIALISTS, OFTEN FOR THE PURPOSE OF INJURY PREVENTION. ALTHOUGH THE FMS MAY FACILITATE THE ABILITY FOR REHAB THERAPISTS AND TRAINERS TO DETERMINE MOVEMENT DYSFUNCTIONS, THE ABILITY TO PREDICT INJURY HAS RECENTLY COME UNDER SCRUTINY. THE FOLLOWING REVIEW EXAMINES THE CURRENT LITERATURE ON THE UTILITY OF THE FMS AS A SCREENING TOOL TO IDENTIFY ATHLETES' RISK FOR INJURY.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Res. 2(2);116-125 (2023) In particular, the recognised relationships between scores obtained in the FMS protocol and the risk of injury in sport should direct the attention of technical staff and medical staff towards the assessment of qualitative movement control (Kraus et al, 2014;Monaco & Schoenfeld, 2019;Newell, 2020). In fact, the Under-17 group shows a score just above the cut-off of the FMS protocol, which identifies a very high injury risk.…”
Section: Discussionmentioning
confidence: 99%
“…Res. 2(2);116-125 (2023) In particular, the recognised relationships between scores obtained in the FMS protocol and the risk of injury in sport should direct the attention of technical staff and medical staff towards the assessment of qualitative movement control (Kraus et al, 2014;Monaco & Schoenfeld, 2019;Newell, 2020). In fact, the Under-17 group shows a score just above the cut-off of the FMS protocol, which identifies a very high injury risk.…”
Section: Discussionmentioning
confidence: 99%
“…Functional movement screen (FMS) is an effective tool to test the quality of athletes' exercise [ 48 ]. The body has 7 basic functional movement modes: squat, hurdle, straight lunge, active straight leg lift, shoulder flexibility, torso stability, and rotational stability [ 49 ]. FMS scores can find the deficiencies in the subjects' physical flexibility and stability to improve them through targeted functional training and reduce the probability of sports injury [ [49] , [50] , [51] , [52] , [53] ].…”
Section: Introductionmentioning
confidence: 99%
“…The body has 7 basic functional movement modes: squat, hurdle, straight lunge, active straight leg lift, shoulder flexibility, torso stability, and rotational stability [ 49 ]. FMS scores can find the deficiencies in the subjects' physical flexibility and stability to improve them through targeted functional training and reduce the probability of sports injury [ [49] , [50] , [51] , [52] , [53] ]. Minick and Kate studied the internal reliability of FMS scores and found that 16 items revealed excellent consistency [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of functional movement is well established in the literature [ 10 , 11 ]. Consequently, the assessment of functional movement, and gaining an understanding of the extent that functional movement relates to other health and sports performance outcomes and injury risk [ 10 , 12 , 13 ], have become key areas of interest for sports medicine and sports science practitioners.…”
Section: Introductionmentioning
confidence: 99%